Educational Impact and Challenges of Online Return Demonstrations in Nursing Education: A Descriptive-Correlational Study - Marjorie D. Coronel; Riena D. Conde; Hezil M. Cagandahan; Fatma D. Datumama; Randy Ian Ferenal Gallego (Universitas Muhammadiyah Surakarta, 2025)
Traditionally, return demonstrations of clinical procedures in nursing education were conducted face-to-face, providing students with hands-on experience crucial for clinical practice. However, due to COVID-19 restrictions, these demonstrations have been shifted to an online or virtual mode. This study explores nursing students' perceptions of performing online return demonstrations, focusing on their educational impact and the challenges encountered. Using a descriptive-correlational design, the study involved 94 purposively selected level three and four students from Mindanao State University – Buug Campus. Data were collected through validity and reliability-tested questionnaires and analyzed using Pearson correlation. Results indicate that while students viewed online return demonstrations positively in terms of content comprehension, they faced significant challenges, including lack of equipment, environmental distractions, suboptimal devices, and time-consuming resource searches. Additionally, insufficient student-teacher interaction and individual assessment further impeded students' performance. A significant correlation (p-value < 0.05) between educational impact and the student’s year level was identified, highlighting that the student’s academic standing influenced perceptions of educational effectiveness. While return demonstrations are now resuming on a face-to-face basis, future crises may necessitate a return to online methods. Therefore, it is crucial to strengthen online teaching-learning approaches to ensure better transfer of learning in similar situations.